The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1142/s2424942417400023
|View full text |Cite
|
Sign up to set email alerts
|

Time-Varying Return Predictability in the Chinese Stock Market

Abstract: China's stock market is the largest emerging market in the world. It is widely accepted that the Chinese stock market is far from e±ciency and it possesses possible linear and nonlinear dependencies. We study the predictability of returns in the Chinese stock market by employing the wild bootstrap automatic variance ratio test and the generalized spectral test. We¯nd that the return predictability vary over time and a signi¯cant return predictability is observed around market turmoils. Our¯ndings are consisten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…It was found that RWH is present but varies in line with the AMH. Further, rolling automatic VR and generalised spectra tests are adopted by Shi, Jiang and Zhou [135] in China using daily and weekly data from 1990 to 2015. They found that the return predictability changes through time and high predictability were discovered around 2007 financial crisis.…”
Section: Time Varying Efficiency Studiesmentioning
confidence: 99%
“…It was found that RWH is present but varies in line with the AMH. Further, rolling automatic VR and generalised spectra tests are adopted by Shi, Jiang and Zhou [135] in China using daily and weekly data from 1990 to 2015. They found that the return predictability changes through time and high predictability were discovered around 2007 financial crisis.…”
Section: Time Varying Efficiency Studiesmentioning
confidence: 99%
“…Firstly, we evaluate the performance of the J − K CSCON portfolios formed by the Chinese A-share individual stocks during the period with both high Table 4: This table reports the performances of the cross-sectional J − K contrarian (CSCON) portfolios during the period with high and low level of different market conditions, including market state (State), market volatility (Volatility), market illiquidity (Illiquidity), and macroeconomic uncertainty (Uncertainty). Estimation period J ∈ {1, 6,12,18,24,30,36,42,48,54, 60} month(s) and holding period K = 1 month, which are presented respectively in first two columns. Monthly average returns of the CSCON portfolios during the whole sample period from 1990 to 2014 are also reported in third column, Raw Return, against which the CSCON profitability for periods with high and low level of each market condition can compare.…”
Section: Context-dependent Csmom and Cscon Effectsmentioning
confidence: 99%
“…As with the samples in studying time-varying risk-premium relation, we take the CSCON portfolios with varying estimation period J and fixed holding period K as samples. J ∈ {1, 6,12,18,24,30,36,42,48,54, 60} month(s) and K = 1 month. We employ several market condition factors that are frequently used in the previous literature [15], including market state, market volatility, market illiquidity, and macroeconomic uncertainty.…”
Section: Statementioning
confidence: 99%
“…Different phenomena not explained by the EMH can be justified from Adaptive Market Hypothesis (AMH) and the Fractal Market Hypothesis (FMH). Studies like Kim, Lim and Shamsuddin [ 5 ] for the US data, Shi, Jiang, Zhou [ 6 ] for the Chinese market, Árendáš and Chovancová [ 7 ] for the very known group of Brazil, Russia, India and China, studied predictability and concluded consistency with the AMH. In the case of the Nigerian stock market, Adaramola and Obisesan [ 8 ] found out linear and non-linear predictability and unpredictability periods, i.e., they establish that this market is not efficient and follows the concept of Adaptive Market Hypothesis.…”
Section: Introductionmentioning
confidence: 99%